2006
DOI: 10.1016/j.comgeo.2005.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The minimum Manhattan network problem: Approximations and exact solutions

Abstract: Given a set of points in the plane and a constant t ≥ 1, a Euclidean t-spanner is a network in which, for any pair of points, the ratio of the network distance and the Euclidean distance of the two points is at most t. Such networks have applications in transportation or communication network design and have been studied extensively. In this paper we study 1-spanners under the Manhattan (or L 1-) metric. Such networks are called Manhattan networks. A Manhattan network for a set of points is a set of axis-paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…Although the correctness proof of their algorithm is incomplete [3], the paper showed that checking the existence of a Manhattan path for O(n) specific pairs of points, instead of O(n 2 ) pairs in T × T , is sufficient for determining whether a given network is a Manhattan network. Following this idea, Benkert et al [1,2] proposed an O(n log n)-time 3-approximation algorithm. They also described a mixed-integer programming (MIP) formulation of the MMN problem.…”
Section: Historical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the correctness proof of their algorithm is incomplete [3], the paper showed that checking the existence of a Manhattan path for O(n) specific pairs of points, instead of O(n 2 ) pairs in T × T , is sufficient for determining whether a given network is a Manhattan network. Following this idea, Benkert et al [1,2] proposed an O(n log n)-time 3-approximation algorithm. They also described a mixed-integer programming (MIP) formulation of the MMN problem.…”
Section: Historical Reviewmentioning
confidence: 99%
“…Most combinatorial constructions [1,2,6,11] rely on the decomposition of the input, by partitioning the plane into several blocks (ortho-convex regions) that can be solved independently. Kato et al [8] presented an O(n 3 )-time 2-approximation algorithm.…”
Section: Historical Reviewmentioning
confidence: 99%
“…We continue with the notion of a generating set introduced in [6] and used in approximation algorithms from [1,8]. A generating set is a subset F of pairs of terminals (or, more compactly, of their indices) with the property that a rectilinear network containing l 1 -paths for all pairs in F is a Manhattan network on T. For example, F ∅ consisting of all pairs i, j with R i,j empty is a generating set [6].…”
Section: Lemma 24 the Edges Of ∂P Belong To Any Minimum Manhattan Nementioning
confidence: 99%
“…Conversely, let x e , e ∈ E, be a feasible solution for (1). Considering x e 's as capacities of the edges e of Γ, and applying the covering constraints and the Ford-Fulkerson's theorem to each network Γ i,j , (i, j) ∈ − → F , oriented as described below, we conclude the existence in Γ i,j of an integer (t i , t j )-flow of value 1, i.e., of an l 1 -path between t i and t j .…”
Section: Lemma 24 the Edges Of ∂P Belong To Any Minimum Manhattan Nementioning
confidence: 99%
See 1 more Smart Citation